PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMP NEGERI 4 MANDAU - Monica Ayu Putri; Rini Dian Anggraini; Titi Solfitri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The background of this study is students low in mathematical of VII grade at SMP Negeri 4 Mandau. The aimed of study is to find out whether there is significant effect of using “problem based learning model” toward students mathematical of VII grade at SMP Negeri 4 Mandau. The study employed the pre-experimental research focus on the static group comparison study design. The sampling of technique was purposive. The samples were two classes that have been purposive sampling after normality test and homogeneity test with the class as an experimental class and control class as a class. There were two sampling in this study; the experimental class was using “problem based learning model” and the control class with scientific approach learning. Data analysis technique used was t-test . Based on the final results of data processing obtained t > t table (1.714 > 1.666) meaning that the application of methods of problem based learning affect learning outcomes in mathematics class VII SMP Negeri 4 Mandau on the material algebra. The finding of this research showed experimental class better than control class (78.13 > 71.13). So, it can be concluded there was significant effect of using problem based learning model toward student’s mathematical of VII grade at SMP Negeri 4 Mandau on the first semester academic years 2016/2017 on the material algebra.Key Word : The result of mathematical, problem based learning model, pre-experimental research.